Smashing Hitler's Panzers : The Defeat of the Hitler Youth Panzer Division in the Battle of the Bulge /: The Defeat of the Hitler Youth Panzer Division in the Battle of the Bulge. (2018) - Zaloga, Steven
No abstract available